Robust beamforming algorithm for RIS-MIMO system based on train prior information - ZHANG Zepeng; LI Cuiran; WU Hao; XIE Jianli; XU Qiong (Tongxin xuebao)
In response to the difficulty in obtaining perfect channel state information (CSI) in high mobility scenarios leaded to the deterioration of the performance of reconfigurable intelligent surface multiple-input multiple-output (RIS-MIMO) system’s active and passive beamforming algorithms issue, a communication model for millimeter-wave MIMO relay in high-speed railways assisted by RIS was constructed. Firstly, with incomplete train position information, the statistical characteristics of the line of sight (LOS) angle estimation error between RIS and mobile relay node (MRN) were estimated and derived. Secondly, the outage performance of the millimeter-wave MIMO system was studied, and an expression of outage probability based on channel capacity was given. Finally, the optimization problem was modelled as a minimum outage probability problem constrained by base station transmit power. To solve this problem, a complex circle manifold optimization algorithm based on accelerated riemann conjugate gradient was proposed. Simulation results show that the proposed algorithm has faster convergence speed and higher system robustness by comparing it with the existing algorithms and the traditional without RIS system, as well as the high-speed railway (HSR) communication system under RIS random phase adjustment.